"Ostrich is a Fowl for any Matter": The ostrich as a "strange" fowl in Jewish literature - Shemesh, Abraham O. (HTS teologiese studies, 2018)
The size, strange body shape and behaviour of the ostrich aroused the imagination of the ancients, Jews and non-Jews, and therefore beginning from the classical era until recent generations, various legends and beliefs were attached to it. The ancients deliberated whether the ostrich is a bird or it is a cross between a bird and a four-legged creature. In this case, Jewish writings reflected an advanced and sometimes independent conception that the ostrich is a bird. A belief that is indeed partially based on reality has to do with the food of the ostrich. In ancient sources, the ostrich is described as eating glass or metal, and according to some testimonies, this is a major component of its food. Medieval literature includes another common belief that the ostrich is gifted with miraculous powers of sight and it can use these powers to hatch the eggs by staring at them. The general impression formed from the study is that the Jews were aware of legends that existed among the nations, and even used them in their study halls for halakhic discussions and to enrich their spiritual world.